A multiple comparative institutional case study exploring the extent to which final year B. Ed. students are prepared for ICT usage in the classroom - Mofokeng, Palesa M. (My University, 2022)
The digital era brought with it sophisticated ATMs (automated teller machines) in their different forms. These ATMs go beyond the banking sector and are sophisticated as you cannot perform or process any task without instructing them to do so. Such ATMs are what we refer to as ICTs – Information Communications Technology. Now, in a world that is constantly evolving as technology continues to advance, the schooling sector is amongst those that face unique challenges. In line with this study, these challenges are inclusive of, but not limited to, professional Information Communications Technology (ICT) teacher training and development. The dominant narrative around this challenge is lack of sufficient professional training for teachers (in-service and pre-service), often inconclusive frameworks and official policies on ICT teacher preparedness. Despite these challenges, the Department of Basic and Higher Education along with higher education institutions (HEIs) continue to establish policies and curriculums that address the challenges at the use and implementation of ICTs as far as initial teacher training is concerned. In order to explore the extent to which final year Bachelor of Education students are prepared to use ICTs in the classroom, a multiple case study and qualitative research method were employed. A link to the study questionnaire was sent followed by semi-structured virtual discussions with twelve (four students from each university) final year students from three purposefully selected South African universities. Three official policies on initial teacher training and ICT and teacher preparedness and the respective institution’s B.Ed. curriculums were analysed. Even though majority of students come from technology destitute backgrounds, the findings point out that, universities are one of the biggest ‘equalizers’ in as far as technologically preparing students from different social circumstances are concerned. Secondly, official policies are being adhered to and applied within institutional context. The study recommends that more research case studies focusing on initial teacher preparedness as far as ICTs in education are concerned be conducted so that the HEI space gets to constantly reflect, self-correct and improve on their implementation measures in attempt to preparing teachers to using ICTs in the classroom.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Education to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022